Independent Press and the Fall of Robert Mugabe: Some Empirical Reflections - Takunda Maodza (Journalism and Media, 2025)
This comparative case study interrogates how Zimbabwe’s independent press reported on ZANU-PF factionalism in the period from 2014 to 2017. It focuses on two dailies, Daily News and NewsDay. These were Zimbabwe’s only privately owned newspapers at the time. The other daily newspapers were The Herald and Chronicle, whose editorial was controlled by the Zimbabwe African National Union Patriotic Front (ZANU-PF) government of Robert Mugabe. Whereas scholarship on ZANU-PF factionalism and the press is still burgeoning, little has been studied about how the independent press reported on Mugabe’s succession. The study is guided by framing theory. Data were gathered through archival research and in-depth face-to-face interviews with purposively selected journalists at Daily News and NewsDay who published stories on Mugabe’s succession. Findings reveal that rival ZANU-PF factions captured bribed journalists and influenced how they reported on Mugabe’s succession. Journalism grew “factionalized” (biased) as reporters became agents of the rival ZANU-PF factions. This disabled the newspapers from playing their informative and educative roles effectively. The factionalized reports left Zimbabweans ill-informed about developments in the governing party.